Association Between the TP53 Polymorphisms and Breast Cancer Risk: An Updated Meta-Analysis - Zhao, Lin; Yin, Xiang-Xiongyi; Qin, Jun; Wang, Wei; He, Xiao-Feng (Frontiers in Genetics, 2022)
Background: The relationship of TP53 codons 72, IVS3 16 bp, and IVS6+62A>G polymorphisms with breast cancer (BC) risk have been analyzed in seventeen published meta-analyses. However, the credibility of statistically significant associations was ignored and many new studies have been reported on these themes. Objectives: To explore whether TP53 codons 72, IVS3 16 bp, and IVS6+62A>G polymorphisms are associated with BC risk and the clinical phenomena. Methods: In order to comprehensively search the data (through October 25, 2021), we provided a clear search strategy and reviewed the references of published meta-analyses. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) were used. Results: The current meta-analysis had a larger sample size than the previous ones: 99 studies with 43,951 BC and 48,479 controls for TP53 codon 72 polymorphism, 35 studies with 8,705 BC and 7,516 controls for IVS3 16 bp polymorphism and 25 studies with 12,222 BC and 12,895 controls for IVS6+62A>G polymorphism. Five gene models were used to explore the association between the three polymorphisms and BC risk, and partial positive results were similar to published meta-analyses results. However, a large number of significant results were considered to be unreliable after correcting with Bayesian false-discovery probability (BFDP), except for the association between TP53 IVS3 16 bp polymorphism and BC risk in overall analysis (GG vs. CC: BFDP = 0.738), matched studies (GG vs. CC: BFDP = 0.173; GG vs CC + CG: BFDP = 0.447) and tumor size below 2cm (GG vs. CC: BFDP = 0.088; GG + CG vs CC: BFDP = 0.730; GG vs CC + CG: BFDP = 0.311). These unreliable results were confirmed again without new solid results emerging in further sensitivity analysis (only studies in compliance with quality assessment standard). Conclusion: After considering the quality of the included studies and the reliability of the results, the present meta-analysis suggested that TP53 codons 72, IVS3 16 bp, and IVS6+62A>G polymorphisms were not significantly associated with the BC risk. Those results which prove that these three polymorphisms increase BC risk are more likely to be false positive results due to various confounding factors.